Chronic pancreatitis - Kleeff, Jörg H.; Lerch, Markus M.; Neoptolemos, John P. (Nature reviews. Disease Primers, 2017)
Chronic pancreatitis is defined as a pathological fibro-inflammatory syndrome of the pancreas in individuals with genetic, environmental and/or other risk factors who develop persistent pathological responses to parenchymal injury or stress. Potential causes can include toxic factors (such as alcohol or smoking), metabolic abnormalities, idiopathic mechanisms, genetics, autoimmune responses and obstructive mechanisms. The pathophysiology of chronic pancreatitis is fairly complex and includes acinar cell injury, acinar stress responses, duct dysfunction, persistent or altered inflammation, and/or neuro-immune crosstalk, but these mechanisms are not completely understood. Chronic pancreatitis is characterized by ongoing inflammation of the pancreas that results in progressive loss of the endocrine and exocrine compartment owing to atrophy and/or replacement with fibrotic tissue. Functional consequences include recurrent or constant abdominal pain, diabetes mellitus (endocrine insufficiency) and maldigestion (exocrine insufficiency). Diagnosing early-stage chronic pancreatitis is challenging as changes are subtle, ill-defined and overlap those of other disorders. Later stages are characterized by variable fibrosis and calcification of the pancreatic parenchyma; dilatation, distortion and stricturing of the pancreatic ducts; pseudocysts; intrapancreatic bile duct stricturing; narrowing of the duodenum; and superior mesenteric, portal and/or splenic vein thrombosis. Treatment options comprise medical, radiological, endoscopic and surgical interventions, but evidence-based approaches are limited. This Primer highlights the major progress that has been made in understanding the pathophysiology, presentation, prevalence and management of chronic pancreatitis and its complications.